Annual arts fundraiser takes patrons to paradise (Raton, NM Raton Range, 1994)
This article is about the Arts Council inviting patrons to a 'Night in the Caribbean' at its third annual fundraising BASH.
Newspaper article
Master list item #: 46
File location is in the Raton file Cabinet
Keywords: Steel Bandits -- Performance Troupe; Old Pass Gallery; Fundraising; Art and Humanities Council; Live Performance; Music Performance; Raton Convention Center; Raton, New Mexico